2019
DOI: 10.3153/fh19020
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Nutrition Habits of Students of the Faculty of Health Sciences

Abstract: Bu araştırma, Gümüşhane Üniversitesi Sağlık Bilimleri Fakültesi'nde okuyan (17-30 yaş; 10.7 ±1.7 yıl) öğrencilerin beslenme alışkanlıklarının saptanması amacıyla planlanmıştır. Öğrencilerin (n=1271) %69.6'sı kız, %30.4'ü erkektir. Araştırma verileri yüz yüze görüşme tekniği kullanılarak anket formu yardımı ile toplanmış, araştırmacılar tarafından hazırlanan anket formu sosyo-demografik özellikler, beslenme alışkanlıkları ve besin tüketim sıklığı bilgilerini içermektedir. Beden Kütle İndeksleri'ne (BKİ) göre; ö… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…While 45.8% (n=178) of 389 study participants who were aware of the term "probiotic" reported using them in our study, the percentage for adults was reported as 73.6% (Arduzlar Kağan et al, 2019). In one study, the rate was determined to be 73.5% (n=446), and in another, the rate was determined to be 82.4% (n=593) (Horasan et al, 2021;Arpa Zemzemoğlu et al, 2019b). Özgül et al (2020) stated that the probiotic consumption rate was 96% (n=24).…”
Section: Resultsmentioning
confidence: 54%
See 2 more Smart Citations
“…While 45.8% (n=178) of 389 study participants who were aware of the term "probiotic" reported using them in our study, the percentage for adults was reported as 73.6% (Arduzlar Kağan et al, 2019). In one study, the rate was determined to be 73.5% (n=446), and in another, the rate was determined to be 82.4% (n=593) (Horasan et al, 2021;Arpa Zemzemoğlu et al, 2019b). Özgül et al (2020) stated that the probiotic consumption rate was 96% (n=24).…”
Section: Resultsmentioning
confidence: 54%
“…In another study conducted for working people, 96% of the participants stated that they knew the term probiotic (Özgül et al, 2020). Arpa Zemzemoğlu et al (2019b), in their study for university students, 55.6% of the participants stated that they knew what probiotics were.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Özyazıcıoğlu et al, (2009) reported in their study that the most skipped meals of the participants were breakfast and lunch [17]. Zemzemoğlu et al, (2019) examined the determinants of the nutritional habits of health sciences students and reported that the most skipped meal by the students was lunch [18]. Similarly, Bayramoğlu et al, (2018) in a study examining the nutritional habits of female academicians, stated that the most skipped meal was lunch, and the reason for skipping a meal was not finding the opportunity [19].…”
Section: Discussionmentioning
confidence: 99%